Дослідження могильника висоцької культури біля с. Мильне на Тернопільщині - Ільчишин, В.В. (Археологічні дослідження в Україні, 2010)
Information about research of Vysotska culture burial ground near Mylne village of Zboriv Region in Ternopil Oblast is presented.